Pembelajaran Bahasa Arab Melalui Metode Penerjemahan Arab-Indonesia Dalam Syair Syaikh Ahmad Bin Yahya An-Najmiy - Ahmad kirom; Siti ngaisah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to describe and describe the techniques and methods of translating Arabic into Indonesian in Syaikh Ahmad Bin Yahya An-Najmiy's poetry. This research uses descriptive analysis method and qualitative approach. The source of the data in this study was a YouTube video with a duration of 1 minute 48 seconds from the